2020
DOI: 10.1515/med-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00152 promotes laryngeal cancer progression by sponging miR-613

Abstract: AbstractBackgroundLong noncoding RNA (lncRNA) LINC00152 (CYTOR) has been reported to be upregulated and to serve as a diagnostic biomarker in multiple types of cancers, including laryngeal squamous cell cancer (LSCC). However, the functional role and molecular mechanisms of LINC00152 in LSCC progression need to be further investigated. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Accumulating studies have revealed the extensive interactions among lncRNA-miRNA-mRNA regulatory pathways involving ceRNAs, wherein lncRNAs can recover the expression and roles of miRNAs by sequestering miRNAs. [49][50][51] In our study, we used bioinformatics analysis to screen putative miRNAs that may interact with C1QTNF1-AS1. MiR-484 was identified to potentially interact with C1QTNF1-AS1, and this prediction was confirmed using the luciferase reporter and RIP assays.…”
mentioning
confidence: 99%
“…Accumulating studies have revealed the extensive interactions among lncRNA-miRNA-mRNA regulatory pathways involving ceRNAs, wherein lncRNAs can recover the expression and roles of miRNAs by sequestering miRNAs. [49][50][51] In our study, we used bioinformatics analysis to screen putative miRNAs that may interact with C1QTNF1-AS1. MiR-484 was identified to potentially interact with C1QTNF1-AS1, and this prediction was confirmed using the luciferase reporter and RIP assays.…”
mentioning
confidence: 99%
“…CYTOR, also known as LINC00152, is a lncRNA with a length of 828 nucleotides and expressed abnormally in many cancers, such as lung cancer, stomach cancer, colon cancer, etc. [15][16][17][18]. It is reported that CYTOR is a key lncRNA in regulating age-related articular cartilage degradation, and CYTOR expression was significantly reduced in the cartilage tissues of OA patients compared to normal samples [9].…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, lncRNA has a crucial role in LSCC progression. For instance, lncRNA FOXD2-AS1 was shown to enhance chemotherapy resistance in LSCC by activating STAT3 [18], and LncRNA LINC00152 can promote laryngeal cancer progression by sponging MiR-613 [19]. However, due to the limited number of screened IALs, many potential and valuable IALs still need to be identi ed to improve the predictive accuracy for LSCC patients.…”
Section: Discussionmentioning
confidence: 99%